2008
DOI: 10.4049/jimmunol.181.4.2772
|View full text |Cite
|
Sign up to set email alerts
|

Human Airway Smooth Muscle Promotes Human Lung Mast Cell Survival, Proliferation, and Constitutive Activation: Cooperative Roles for CADM1, Stem Cell Factor, and IL-6

Abstract: The microlocalization of mast cells within specific tissue compartments is thought to be critical for the pathophysiology of many diverse diseases. This is particularly evident in asthma where they localize to the airway smooth muscle (ASM) bundles. Mast cells are recruited to the ASM by numerous chemoattractants and adhere through CADM1, but the functional consequences of this are unknown. In this study, we show that human ASM maintains human lung mast cell (HLMC) survival in vitro and induces rapid HLMC prol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
111
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 100 publications
(120 citation statements)
references
References 46 publications
6
111
1
Order By: Relevance
“…We have reported previously that HLMCs and HMC-1 cells in vitro adhere to ASM, in part via CADM1 (14), and in coculture with ASM mast cells survive and proliferate (23). In contrast, we report in this paper that the mast cell transition toward a fibroblastoid phenotype was CADM1 independent.…”
Section: Discussioncontrasting
confidence: 50%
See 1 more Smart Citation
“…We have reported previously that HLMCs and HMC-1 cells in vitro adhere to ASM, in part via CADM1 (14), and in coculture with ASM mast cells survive and proliferate (23). In contrast, we report in this paper that the mast cell transition toward a fibroblastoid phenotype was CADM1 independent.…”
Section: Discussioncontrasting
confidence: 50%
“…Histamine was measured by a sensitive radioenzymatic assay, as described previously, and corrected for cell number (23).…”
Section: Quantification Of Histamine Release By Mast Cellsmentioning
confidence: 99%
“…It is therefore likely that the migration of mast cells is under the control of several chemokines. Previous studies have demonstrated that a number of chemotactic factors such as CCL5, CCL11, CX3CL1, IL-8, IL-6 contributed to regulate the migration of human mast cells (Nilsson et al, 1999;Juremalm et al, 2002;El-Shazly et al, 2006;Hollins et al, 2008;Zweifel et al, 2010).In this study, we found that chemokines including CCL5, CCL11, CX3CL1, and IL-8 were up-regulated in the epithelial cells of nasal polyps, but IL-6 was not expressed by nasal epithelial cells. This indicated that these chemokines except for IL-6, released from epithelial cells of nasal polyps may be responsible for the migration of mast cells toward the epithelium in nasal polyps.…”
Section: Discussionsupporting
confidence: 61%
“…Recent studies have reported that bronchial and blood vessel smooth muscle cells have the ability to produce SCF in the normal state [6,7]. These findings suggest that intestinal smooth muscle cells have the ability to enhance SCF production in response to immunological stimuli.…”
mentioning
confidence: 70%
“…This suggests that the intestinal smooth muscle cells enhanced SCF production against nematode infection locally, and this enhanced SCF production may have led to an increase in mast cell numbers [12]. Several researchers have hypothesized that smooth muscle cells are SCF producing cells, because mast cells increase within the bronchial smooth muscle layers, and within the interstitial tissues beside the blood vessels of lung, in patients sensitized to common allergens [6,7]. These results demonstrate that cultured smooth muscle cells can produce SCF, however, it has not been known whether smooth muscle cells can enhance SCF production in response to the pathological stimuli that induce increases in mast cell numbers.…”
mentioning
confidence: 99%